The Impact of a public health environmental contingency (COVID-19) on Stress and a General Health of workers from different industrial sector. - Ibarra, Victor (Archives of Business Research, 2021)
Abstract. The problems that arise in society, in relation to health affect workers to some extent, this is the case of the COVID -19 pandemic, which has somehow affected organizations in general, such as: in their profits, in the reduction of personnel, in adapting new forms of work if required, and in activating health protocols to avoid the spread of it in its workers, this health situation that is present worldwide has had a great impact on people from the psychological aspect, it is for this the interest to carry out this research, with the purpose of knowing the perception of the workers of different organizations in this pandemic situation, that is to say, how it has affected them in relation to stress and therefore their general health, the instruments applied were: Perceived Stress Scale (10 items) and the Goldberg General Health Questionnaire. The results of this work gave us a Cronbach alpha of α = .85 of reliability which indicates that this study is reliable, likewise 60% of the population report that they have felt stress due to COVID-19, as well as 42% of the population state that they have perceived factors or symptoms that affect their mental health to some degree.